Financial security - Marieke de Goede (Finance and Society, 2017)
This essay was originally published in The Routledge Handbook of New Security Studies (Burgess, 2010), and has since become a key reference point in debates on the finance-security nexus. It is reproduced here as a starting point for the present forum, which aims to further advance efforts to conceptualise the relations between finance and security.
Keywords: 300